Direct analysis of biodiesel microemulsions using an inductively coupled plasma mass spectrometry - Amais, Renata S.; Garcia, Edivaldo E.; Monteiro, Marcos R. [UNESP]; Nogueira, Ana Rita A.; Nobrega, Joaquim A. (Elsevier B.V., 2010)
An analytical procedure for direct introduction of biodiesel samples into an inductively coupled plasma mass spectrometer (ICP-MS) by using microemulsion for sample preparation was developed here. Cadmium, Co, Cu, Mn, Ni, Pb, Ti, and Zn were determined in biodiesel microemulsified samples prepared from different oleaginous sources (African palm, castor beans, palm, soybeans and an unknown oleaginous). Microemulsions were prepared using 0.25 mL Triton X-100, 0.25 mL 20% v v(-1) HNO(3), 0.50 mL biodiesel sample and 4.0 mL n-propanol. Argon-oxygen mixture was added to the plasma as auxiliary gas for correcting matrix effects caused by the high carbon load due to biodiesel microemulsions. The oxygen gas flow rate was set in 37.5 mL min(-1). The accuracy of the developed procedure was evaluated by applying addition-recovery experiments for biodiesel samples from different sources. Recoveries varied from 76.5 to 116.2% for all analytes but Zn in castor beans biodiesel sample (65.0 to 76.2%). Recoveries lower than 86.6% were obtained for palm biodiesel sample, probably due to matrix effects. Detection limits calculated by using oxygen in the composition of the auxiliary gas added to the plasma were higher than those calculated without using it, probably due to the highest formation of oxides. Despite oxides formation, best analytical performance was reached by using oxygen as auxiliary gas and by proper correction of transport interferences. The developed procedure based on microemulsion formation was suitable for direct introduction of biodiesel samples in ICP-MS. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Biodiesel; Microemulsions; ICP-MS; Auxiliary gas; Oxygen